Genetic Differentiation of Geographically Overlapping Sister Species of Eucalyptus in Northern Australia - Harvey K. Orel; Todd G. B. McLay; Daniel J. Murphy; David J. Cantrill; Frank Udovicic; Patrick S. Fahey; Donald C. Franklin; Donna Lewis; Philip G. Docherty; Adam White; Michael J. Bayly; Rachael M. Fowler (Ecology and Evolution, 2025)
ABSTRACT In the large genus Eucalyptus, which dominates most of Australia's open forests and woodlands, genetic studies commonly show signs of introgression between closely related, co‐occurring species. Here we assessed genetic variation in two sister species with geographically overlapping distributions in northern Australia. One species, Eucalyptus tetrodonta, is a dominant species in many lowland savannas. It is found on gravelly red‐lateritic to sandy soils, with a large distribution spanning over 2000 km east‐to‐west and 1000 km north‐to‐south, from the Kimberley region of Western Australia to northern Queensland. The other, E. megasapala, was taxonomically separated from E. tetrodonta in 2006 on the basis of its larger sepals, prominently ribbed buds and operculum, and fruit and peduncle shape. It typically occurs on rocky substrates in northeast Queensland, within the range of E. tetrodonta, where the two species can form stands within a few hundred metres of one another. Contrary to expectations, DArTseq genotyping showed strong differentiation between the two species (FST: 0.28) and little evidence of genetic admixture. Analyses of data from the Australasian Virtual Herbarium showed significant differences in flowering times between the two species. SNP outlier analyses identified multiple loci potentially under selection that are associated with differences between the two species, including the gene FT‐interacting protein 7 (FTIP7), which is known to modulate flowering time in plants. Based on current data, it is unclear whether differentiation of these species is the product of parapatric/sympatric speciation or if it was allopatric with secondary geographic overlap. Within E. tetrodonta, genetic variation showed a strong signal of isolation‐by‐distance, with an east–west trend in the pattern of genetic relatedness. The most substantial genetic break in E. tetrodonta was associated with the Carpentarian Gap, a region of seasonally arid, alluvial plains on the southern margin of the Gulf of Carpentaria known as a biogeographic barrier for other Australian biota.